DEVELOPING POP – UP BOOK MEDIA IN TEACHING AND LEARNING DESCRIPTIVE TEXT TO IMPROVE WRITING SKILL - Susani, Maratus Susani; Makrifah, Istina Atul; Rofiah, Siti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
This research was carried out based on process and the results of observation at SMP Nabawi Maftahul Uluum. This research was aimed to Developing Pop – Up Book Media in Teaching and Learning Descriptive Text to Improve Writing Skill in 7th Grade of SMP Nabawi Maftahul Uluum. Researcher used method used is ADDIE method where researcher conducted five steps. The steps include analysis, design, development, implementation, evaluation. . This research was conducted at SMP Nabawi Maftahul Ulum with the research subject in 7th grade. This pop-book media is composed of materials, functions, characteristics, and examples. Equipped with Pop-Up Image as practice material for writing descriptive text. Data collection techniques were carried out using interviews and surveys. The instruments used are interview guidelines and questionnaires using a Likert scale. Based on the results of the validation carried out by material expert and media expert, linguists then the results of teacher and student responses, the percentage of results obtained were 91.8%, 92.2%, 94.14%, 96.45 and 90.8% with a total score of 93% where the value reaches the criteria of